KONSEP ADMINISTRASI PENDIDIKAN - Meti Fatimah; Ikke Fitriana Nugrahini; Nur Ali Rahmatullah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The entire set of actions taken to achieve a goal-from organizing to managing everything-is called administration. Exercises such as taking notes, writing letters, and other comparative exercises are undeniably referred to as administration. Every business, office, and organization has an arrangement framework because of this. Where professionals referred to as administrators or administrative staff carry out these responsibilities. The writing of this paper uses a concentration of writing on strategies with the method of gathering information through literature studies obtained from books, and articles in diaries related to the topic and discussion. The term